Decreasing The Intensity of Primary Dysmenorhoea by Giving Low Fat Liquid Milk to Students of Health Polytechnic the Ministry of Health Malang - Kurniyanti, Meiranda Tria; Bachri, Syaiful; Kiswati, Kiswati (D'Nursing and Health Journal (DNHJ), 2023)
Background:Primary dysmenorrhea is pain that is felt during menstruation due to endometrial hypertonicity and vasoconstriction resulting in ischemia and pain in the lower abdomen. Method: The research design uses Pre Experimental (One Group Pre Test Post Test). The population of this study is 62 students. In selecting the sample using the Simple Random Sampling method, a sample of 56 students was obtained. Data analysis used the Wilcoxon test. Results: Tshe results obtained were that out of 45 students, 40 students (88.9%) experienced primary dysmenorrhea and 5 students (11.1%) did not experience dysmenorrhea at during menstruation. The aim of this research is to analyze the decrease in the intensity of primary dysmenorrhea by giving low fat liquid milk to students of the Ministry of Health Malang Jember Bachelor of Midwifery Study Program. Most students after being given low fat liquid milk experienced moderate and mild dysmenorrhea. The results of the statistical analysis showed that there was a significant decrease in the intensity of primary dysmenorrhea in students before and after being given low fat liquid milk, with a p-value of 0.000 <0.05, because the p-value <α. Conclusion: So it can be concluded that giving low fat liquid milk can reduce the intensity of primary dysmenorrhea. Low fat liquid milk can be used as a non-pharmacological treatment to reduce the pain intensity of primary dysmenorrhea.The abstract should be clear, concise and descriptive.